2016
DOI: 10.3390/molecules21101343
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Autophagy by a Thioxanthone Decreases the Viability of Melanoma Cells

Abstract: (1) Background: Our previous studies unveiled the hit thioxanthone TXA1 as an inhibitor of P-glycoprotein (drug efflux pump) and of human tumor cells growth, namely of melanoma cells. Since TXA1 is structurally similar to lucanthone (an autophagy inhibitor and apoptosis inducer) and to N 10 -substituted phenoxazines (isosteres of thioxanthones, and autophagy inducers), this study aimed at further assessing its cytotoxic mechanism and evaluating its potential as an autophagy modulator in A375-C5 melanoma cells;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…Cell autophagy can not only eliminate the metabolic products of cells and abnormal intracellular proteins, but can also degrade redundant or damaged organelles (11). Autophagy can be induced during early newborn development, hypoxia, infection and hunger, and its degradation products can provide materials and energy for cells, thus maintaining cell homeostasis (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell autophagy can not only eliminate the metabolic products of cells and abnormal intracellular proteins, but can also degrade redundant or damaged organelles (11). Autophagy can be induced during early newborn development, hypoxia, infection and hunger, and its degradation products can provide materials and energy for cells, thus maintaining cell homeostasis (22).…”
Section: Discussionmentioning
confidence: 99%
“…The autophagy-related genes are critical factors that regulate the process of autophagy (10). The primary functions of autophagy are to eliminate biological waste materials within the body and to promote metabolism by degradation of damaged organelles under stress conditions, such as hunger, which aids in the self-protection of cells and promotes cell survival (11). However, excessive autophagy decreases cell survival by promoting autophagic cell death (11).…”
Section: Introductionmentioning
confidence: 99%
“…During the last few decades there has been widespread interest in oxygenated heterocyclic compounds such as molecules with a xanthone scaffold [ 1 , 2 , 3 ], mainly in consideration of their important roles as bioactive agents and because xanthone is an attractive core for molecular modifications [ 4 , 5 , 6 , 7 , 8 , 9 ] and the design of new molecular entities [ 10 , 11 ]. Xanthonic derivatives can be isolated from terrestrial [ 12 , 13 ] and marine [ 2 ] sources, or obtained by synthesis using different synthetic methodologies [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that a synthetic hit thioxanthonic molecule (1-{[2-(diethylamino)ethyl]amino}-4-propoxy-9H-thioxanthen-9-one, TXA1) and its soluble salt (TXA1.HCl), reduced the in vitro growth of a panel of human tumor cell lines, without affecting the growth of non-tumor cells [18,19,20]. Such antitumor effect was shown to involve autophagy modulation in melanoma and breast cancer cells [20]. Nevertheless, the underlying mechanism of action of TXA1.HCl was not fully elucidated, nor was its antitumor potential in vivo verified.…”
Section: Introductionmentioning
confidence: 99%